Sistem Pengaturan Penggunaan Perangkat Listrik Rumah Tangga Menggunakan Komputer Mini Hemat Daya - Hironimus Leong; Suyanto E.A. (Soegijapranata Catholic University, 2019)
Abstract: The use of household electrical appliances can be controlled automatically by utilizing computer that can control when the device is switched on or off according to the schedules and conditions provided by the user. Provisions and schedules can be determined by the user through software management that regulates the date and time regularly or specifically. By utilixing